Disseminated intravascular coagulation - Satoshi Gando; Marcel Levi; Cheng-Hock Toh (Journal of Intensive Care)
Abstract Background Disseminated intravascular coagulation (DIC) is characterized by systemic coagulation activation, anticoagulation pathway impairment, and persistent fibrinolysis suppression, resulting in widespread microvascular thrombosis, followed by hemorrhagic consumption coagulopathy and multiple organ dysfunction syndrome. This article aimed to provide a comprehensive and updated DIC overview. Main body The International Society on Thrombosis and Hemostasis provides definitions, underlying disorders, diagnostic algorithms, and management guidelines for DIC. Two clinical features of DIC are hemorrhagic consumption coagulopathy, characterized by oozing and difficult-to-control bleeding, and microvascular thrombosis, leading to dysfunctions in multiple vital organs. Histones derived from cellular damage play central roles in the innate-immune-based coagulation model, comprising the initiation, amplification, propagation, and reinforcement phases, which, if dysregulated, develop into DIC. Thus, the innate immune-mediated pathogenic pathways in DIC have become clear. Cell death, damage-associated molecular patterns (including histones), crosstalk between hypoxic inflammation and coagulation, and the serine protease network (comprising coagulation and fibrinolysis, the Kallikrein–Kinin system, and complement pathways) play major roles in DIC pathogenesis. Conversely, these pathogenic pathways and DIC synergistically contribute to organ dysfunction, leading to poor prognoses. Effective DIC management requires treating the underlying condition, along with substitution therapies and, in some cases, antifibrinolytics. Anticoagulant use has been extensively debated; however, the selection of optimal target patients could optimize their application and improve patient outcomes in the near future. Conclusions This review provides an updated overview of DIC, aiming to help readers understand various aspects of DIC today.